ANALISIS EMPLOYER BRANDING DAN REPUTASI DALAM MENINGKATKAN INTENTION TO APPLY GENERASI Z (STUDI KASUS PADA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PAMULANG) - Aurellia, Selsa; Agrasadya, Agrasadya (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the role of employer branding and company reputation in increasing the intention to apply among Generation Z. The focus of this research is directed toward final-year students of the Management Study Program, Faculty of Economics and Business, Universitas Pamulang, who are preparing to enter the workforce. This research uses a qualitative approach with data collection techniques that include in-depth interviews with key informants from the academic field and a Focus Group Discussion (FGD) involving nine students with a minimum of two years of work experience. The findings reveal that employer branding delivered through social media serves as the primary factor in attracting students’ attention. Informants stated that they assess a company based on visual content showing daily work activities, workplace image, and the transparency of organizational values. Company reputation is also a significant consideration, especially related to online reviews, institutional accreditation (such as Grade A/B), and perceptions of managerial honesty and professionalism. Meanwhile, the intention to apply tends to emerge when the recruitment process is perceived as transparent, structured, and aligned with their field of interest